PEMODELAN APLIKASI MOBILE MODUL PERKULIAHAN BERBASIS CLIENT SERVER - Rabby Nazli (Universitas Islam Kuantan Singingi, 2018)
The faster technological development makes it easier for us to carry out life activities more easily. currently mobile applications have not been used so much in a lecture that an application is needed that can meet these shortcomings. For that I try to model a mobile application that can help lecturers and students in sharing learning material at each meeting so as to facilitate the process of a lecture. Which is based on client server where this application can change its data at any time according to the user's height and will be modeled using the Unifield Modeling Language (UML) tool.